2014
DOI: 10.1371/journal.pone.0115319
|View full text |Cite
|
Sign up to set email alerts
|

Human Brucellosis in Maghreb: Existence of a Lineage Related to Socio-Historical Connections with Europe

Abstract: Despite control/eradication programs, brucellosis, major worldwide zoonosis due to the Brucella genus, is endemic in Northern Africa and remains a major public health problem in the Maghreb region (Algeria/Morocco/Tunisia). Brucella melitensis biovar 3 is mostly involved in human infections and infects mainly small ruminants. Human and animal brucellosis occurrence in the Maghreb seems still underestimated and its epidemiological situation remains hazy. This study summarizes official data, regarding Brucella m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 23 publications
4
34
0
1
Order By: Relevance
“…Despite attempts at eradication, there remain 500000 cases annually worldwide, with many going unreported [1]. Since the 1980s, several outbreaks have occurred in the Ghardaia province, most recently in 2016 [2], at the time of our patient’s exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Despite attempts at eradication, there remain 500000 cases annually worldwide, with many going unreported [1]. Since the 1980s, several outbreaks have occurred in the Ghardaia province, most recently in 2016 [2], at the time of our patient’s exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the human samples originating in Piemonte, although clustered within the West Mediterranean clade (ItBM_99, ItBM_78) were genetically divergent from animal samples, with 162 and 199-allele difference to the closest isolate and could be identified as outliers although distantly related to other Italian genotypes. Epidemiological investigations linked those cases to people who had come from northern African countries where the same West Mediterranean lineage is thought to be prevalent (35). Divergence of these two samples was not however evident in MLVA typing (2-3 alleles of distance to other isolates).…”
Section: Resultsmentioning
confidence: 99%
“…Published bacteriological investigations in Algeria have characterised Brucella at the species and biovar levels. Brucella melitensis biovar 3 is the most prevalent in the case of goats (29). A study of the genetic diversity of Algerian B. melitensis biovar 3 strains by Lounes et al to assess whether an epidemiological relationship existed with European strains was recently carried out (29).…”
Section: The History Of Brucellosis Occurrence and Distributionmentioning
confidence: 99%
“…Brucella melitensis biovar 3 is the most prevalent in the case of goats (29). A study of the genetic diversity of Algerian B. melitensis biovar 3 strains by Lounes et al to assess whether an epidemiological relationship existed with European strains was recently carried out (29). The results showed that the Algerian and European strains cluster together.…”
Section: The History Of Brucellosis Occurrence and Distributionmentioning
confidence: 99%